Determination of robenidine in shrimp and chicken samples using the indirect competitive enzyme-linked immunosorbent assay and immunochromatographic strip assay. Issue 2 (24th November 2020) - Lin, Lu; Song, Shanshan; Wu, Xiaoling; Liu, Liqiang; Kuang, Hua; Xiao, Jing; Xu, Chuanlai
Abstract : In this study, the monoclonal antibody-based indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and an immunochromatographic strip assay were developed for the rapid screening of robenidine hydrochloride (ROBH) in samples. Abstract : In this study, the monoclonal antibody-based indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and an immunochromatographic strip assay were developed for the rapid screening of robenidine hydrochloride (ROBH) in samples. The 50% inhibitory concentration (IC50 ) of ROBH was 0.927 ng mL −1, and the standard curve showed a linear correlation coefficient of 0.99932. There was no cross-reaction between ROBH and other commonly used anticoccidial drugs, which indicated that the monoclonal antibody had high specificity. The recoveries of ic-ELISA were in the range of 87.8% to 102.0%. The immunochromatographic strip assay displayed cut-off values of 10, 5 and 10 ng g −1 for shrimp, chicken breast and chicken liver samples, respectively. In addition, the results can be obtained within 10 min by naked eye observations. And in sample analysis, the results of ic-ELISA and the immunochromatographic strip assay were in accordance with those of LC-MS/MS. Thus, the ic-ELISA and immunochromatographic strip assay are effective methods for the detection of ROBH in shrimp, chicken breast and chicken liver samples.